Chromium (III) Complexes of Esters of Carbazic Acid - Agarwal, Alok; Srivastava , Anupama; Srivastava, Mahesh (Asian Journal of Chemistry, 2010)
Complexes of ethyl and t-butyl esters of carbazic acid with CrX3·nH2O (X ═ NO3–, Cl–, Br–, I–, NCS–) have been prepared and characterized on the basis of vibrational and electronic spectroscopy and magnetic measurements. The bonding occurs through the amino nitrogen and oxygen atom of the ligands. The ligand field parameters have also been calculated.